Importance of abiotic stress as a range‐limit determinant for European plants: insights from species responses to climatic gradients - Signe Normand; Urs A. Treier; Christophe Randin; Pascal Vittoz; Antoine Guisan; Jens‐Christian Svenning (Global Ecology and Biogeography, 2009)
Aim We examined whether species occurrences are primarily limited by physiological tolerance in the abiotically more stressful end of climatic gradients (the asymmetric abiotic stress limitation (AASL) hypothesis) and the geographical predictions of this hypothesis: abiotic stress mainly determines upper‐latitudinal and upper‐altitudinal species range limits, and the importance of abiotic stress for these range limits increases the further northwards and upwards a species occurs. Location Europe and the Swiss Alps. Methods The AASL hypothesis predicts that species have skewed responses to climatic gradients, with a steep decline towards the more stressful conditions. Based on presence–absence data we examined the shape of plant species responses (measured as probability of occurrence) along three climatic gradients across latitudes in Europe (1577 species) and altitudes in the Swiss Alps (284 species) using Huisman–Olff–Fresco, generalized linear and generalized additive models. Results We found that almost half of the species from Europe and one‐third from the Swiss Alps showed responses consistent with the predictions of the AASL hypothesis. Cold temperatures and a short growing season seemed to determine the upper‐latitudinal and upper‐altitudinal range limits of up to one‐third of the species, while drought provided an important constraint at lower‐latitudinal range limits for up to one‐fifth of the species. We found a biome‐dependent influence of abiotic stress and no clear support for abiotic stress as a stronger upper range‐limit determinant for species with higher latitudinal and altitudinal distributions. However, the overall influence of climate as a range‐limit determinant increased with latitude. Main conclusions Our results support the AASL hypothesis for almost half of the studied species, and suggest that temperature‐related stress controls the upper‐latitudinal and upper‐altitudinal range limits of a large proportion of these species, while other factors including drought stress may be important at the lower range limits.